2012
DOI: 10.1590/s0100-204x2012000200020
|View full text |Cite
|
Sign up to set email alerts
|

Meta-análise de parâmetros genéticos relacionados ao consumo alimentar residual e a suas características componentes em bovinos

Abstract: Resumo -O objetivo deste trabalho foi estimar, por meio de meta-análise, a herdabilidade (h 2 ) e as correlações genética (r g ) e fenotípica (r f ) do consumo alimentar residual (CAR), e das suas características componentes, em bovinos de 19 raças ou grupamentos genéticos. Foram utilizados 22 trabalhos científicos publicados entre 1963 e 2011, de oito países, o que totalizou 52.637 bovinos com idades que variaram de 28 dias até a idade de abate. As estimativas de CAR, consumo de matéria seca (CMS), ganho médi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…However, the heritability for days to calving obtained in the present study was higher than that reported for B. taurus (Mu et al, 2016) and B. indicus (Forni and Albuquerque, 2005), whereas the heritability for RFI was lower than either B. taurus (Mu et al, 2016) or B. indicus (Santana et al, 2014). Although the heritabilities estimated using part of the present feed efficient database are high for the traits involved in the calculation of RFI, 0.41 to 0.53 for DMI, ADG, and metabolic midtest weight (Grion et al, 2014;Ceacero et al, 2016), the estimates obtained for RFI are lower than those reported in the literature (Del Claro et al, 2012).…”
Section: Genetic Evaluationcontrasting
confidence: 76%
“…However, the heritability for days to calving obtained in the present study was higher than that reported for B. taurus (Mu et al, 2016) and B. indicus (Forni and Albuquerque, 2005), whereas the heritability for RFI was lower than either B. taurus (Mu et al, 2016) or B. indicus (Santana et al, 2014). Although the heritabilities estimated using part of the present feed efficient database are high for the traits involved in the calculation of RFI, 0.41 to 0.53 for DMI, ADG, and metabolic midtest weight (Grion et al, 2014;Ceacero et al, 2016), the estimates obtained for RFI are lower than those reported in the literature (Del Claro et al, 2012).…”
Section: Genetic Evaluationcontrasting
confidence: 76%
“…Feed efficiency traits, such as residual feed intake and dry matter intake, in Nellore cattle show heritability estimates of 0.30 and 0.41, respectively (Del Claro et al, 2012). In turn, the heritability estimates for meat quality traits, such as back-fat thickness and loin eye area, are 0.24 and 0.33, respectively (Meirelles et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There was no correlated response in weight per year and in weight gain, and the effectiveness of low RFI selection in reducing feed costs was proven without affecting production. The RFI is important because it reduces the direct economic impacts of reduced feed intake, as well as the effects of environmental impact on reducing methane emissions from enteric fermentation of ruminants [5]. Farmers usually select cattle only for their size, and the biggest disadvantage would be the increased energy requirement for the cattle to perform its basic activities such as walking or grazing [6].…”
Section: David Publishingmentioning
confidence: 99%
“…The studies evaluated were related in chronological order (Table 2), with estimation of the heritability (h 2 ) of the RFI characteristic, definition of RFI, number of animals, sex, country, breed and age in which animals were tested, the data were adapted from Del Claro et al [5].…”
Section: Importance and Relevancementioning
confidence: 99%
See 1 more Smart Citation